2012
DOI: 10.1182/blood-2011-12-398537
|View full text |Cite
|
Sign up to set email alerts
|

Stromal SPARC contributes to the detrimental fibrotic changes associated with myeloproliferation whereas its deficiency favors myeloid cell expansion

Abstract: In myeloid malignancies, the neoplastic clone outgrows normal hematopoietic cells toward BM failure. This event is also sustained by detrimental stromal changes, such as BM fibrosis and osteosclerosis, whose occurrence is harbinger of a dismal prognosis. We show that the matricellular protein SPARC contributes to the BM stromal response to myeloproliferation. The degree of SPARC expression in BM stromal elements, including CD146 ؉ mesenchymal stromal cells, correlates with the degree of stromal changes, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 53 publications
(73 reference statements)
5
50
0
2
Order By: Relevance
“…Within the spleen parenchyma, myeloid cells populating the red pulp have been shown to assist B cells in a T cell-independent fashion by releasing trophic and prosurvival factors ( 27 ). Furthermore, our recent fi ndings linked stromal SPARC defi ciency to myeloid cell proliferation in the bone marrow ( 18 ), and the observed myeloid cell skewing in the presence of autoimmunity ( 28 ) suggested that myeloid cell expansion and localization may be altered in lpr/lpr/Sparc −/− . Combining FACS, immunohistochemistry ( IHC), and immunofl uorescence analyses, we observed increases in spleen myeloid cells and myeloid precursors (LK, GMP) in Fas-mutant mice, and these populations were further expanded in the absence of SPARC, confi rming that the Sparc −/− background is permissive for myeloproliferative signals ( Fig.…”
Section: In the Absence Of Sparc Cd5 + B Cells And Myeloid Cells Formentioning
confidence: 92%
See 3 more Smart Citations
“…Within the spleen parenchyma, myeloid cells populating the red pulp have been shown to assist B cells in a T cell-independent fashion by releasing trophic and prosurvival factors ( 27 ). Furthermore, our recent fi ndings linked stromal SPARC defi ciency to myeloid cell proliferation in the bone marrow ( 18 ), and the observed myeloid cell skewing in the presence of autoimmunity ( 28 ) suggested that myeloid cell expansion and localization may be altered in lpr/lpr/Sparc −/− . Combining FACS, immunohistochemistry ( IHC), and immunofl uorescence analyses, we observed increases in spleen myeloid cells and myeloid precursors (LK, GMP) in Fas-mutant mice, and these populations were further expanded in the absence of SPARC, confi rming that the Sparc −/− background is permissive for myeloproliferative signals ( Fig.…”
Section: In the Absence Of Sparc Cd5 + B Cells And Myeloid Cells Formentioning
confidence: 92%
“…Outputs of the automated image analysis relative to the eight microphotographs obtained from the two TMA spots of each case were averaged to obtain the SPARC expression value for that case. Routine hematoxylin and eosin (H&E), Masson's trichrome, and Gomori's silver staining were performed as previously described ( 18 ).…”
Section: Histopathology and Ihcmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it remains elusive how heterogeneous the stromal population is, and whether there is an overlap of Gli1 + and LepR + cells. Another open question is how the identified cell populations compare with CD146 + , SPARC‐expressing cells, which also were shown to react to myeloproliferative stimuli 43, 44. Future single‐cell resolution studies will shed light on this interesting topic.…”
Section: Stromal Cell Populations In Bm Fibrosismentioning
confidence: 99%